Silicon Supplementation Alters the Composition of Herbivore Induced Plant Volatiles and Enhances Attraction of Parasitoids to Infested Rice Plants - Liu, Jian; Zhu, Jiwei; Zhang, Pengjun; Han, Liwei; Reynolds, Olivia L.; Zeng, Rensen; Wu, Jinhong; Shao, Yue; You, Minsheng; Gurr, Geoff M. (Frontiers in Plant Science, 2017)
Silicon (Si) is important in plant defences that operate in a direct manner against herbivores, and work in rice (Oryza sativa) has established that this is mediated by the jasmonate signalling pathway. Plant defences also operate indirectly, by the production of herbivore induced plant volatiles (HIPVs) that attract predators and parasitoids of herbivores. These indirect defences too are mediated by the jasmonate pathway but no earlier work has demonstrated an effect of Si on HIPVs. In this study we tested the effect of Si supplementation versus Si deprivation to rice plants on subsequent HIPV production following feeding by the important pest, rice leaffolder (Cnaphalocrocis medinalis). Gas chromatography–mass spectrometry analyses showed lower production of α -bergamotene, β –sesquiohellandrene, hexanal 2-ethyl and cedrol from +Si herbivore-infested plants compared with -Si infested plants. These changes in plant chemistry were ecologically significant in altering the extent to which parasitoids were attracted to infested plants. Adult females of Trathala flavo-orbitalis and Microplitis mediator both exhibited greater attraction to the HIPV blend of +Si plants infested with their respective insect hosts compared to -Si infested plants. In equivalent studies using RNAi rice plants in which jasmonate perception was silenced there was no change to the HIPV blend associated with Si treatment; indicating that the effects of Si on HIPVs are modulated by the jasmonate pathway. Further, this work demonstrates that silicon alters the HIPV blend of herbivore-infested rice plants. The significance of this finding is that there are no earlier-published studies of this phenomenon in rice or any other plant species. Si treatment to crops offers scope for enhancing induced, indirect defences and associated biological control of pests because parasitoids are more strongly attracted by the HIPVs produced by +Si plants.